Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Kerja Karyawan - Ana Nalia, Ni Kadek; Sadiartha, A.A. Ngurah Gede; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was conducted at the Karma Mayura Hotel in Ubud with the aim of knowing the effect of organizational culture and work motivation on employee performance. The population in this study were all employees of the Karma Mayura Ubud Hotel in 2021 with a total of 45 people. The sample used in this study were 45 respondents, namely all employees of the Karma Mayura Ubud Hotel in 2021. The data analysis technique used in this study was validity, reliability , classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study it can be seen that: (1) Organizational culture has a positive and significant effect on employee performance. (2) Work motivation has a positive and significant effect on employee performance. (3) Organizational culture and work motivation have a positive and significant effect simultaneously on employee performance. The magnitude of the influence of the independent variables on employee morale is 69.1%. Looking at the results of the research, it is hoped that in the future the Karma Mayura Ubud Hotel will routinely hold outing activities in order to form a harmonious relationship between employees so that motivation to work and improve employee performance will grow